Tyconius' Apocalypse Commentary, Its Reconstruction, and Its Significance for Augustine's Doctrine of the Two Cities - Oort, Johannes van (Vigiliae Christianae, 2018)
The present article deals with Roger Gryson's reconstruction of Tyconius' lost Commentary on the Apocalypse (CCL 107A), his subsequent French translation of this reconstructed Commentary (CCT 10), and the English translation Tyconius, Exposition of the Apocalypse by Francis Gumerlock, with long introduction and ample notes by David Robinson (FoC 134). After having reviewed the strenghths and weaknesses of each of these publications, the article concludes with a discussion of the significance of Tyconius' Commentary for the question of the origin of Augustine's two civitates doctrine.